Evaluation on the degree of bitterness of green mussel (Perna viridis) protein hydrolysate / Siti Hafsah Mohd Shah - Mohd Shah, Siti Hafsah (2012)
Properties of protein hydrolysate prepared from green mussel (Perna viridis) by enzymatic hydrolysis using Alcalase® 2.4L at different pH and enzyme to substrate ratio were determined. Hydrolysis was performed using the pH-stat method. Mussel hydrolysate produced at pH 7 with E/S 5% had protein content of 37.17%. Mussel hydrolysate produced at pH 7 had low molecular weight peptide which was < 18 kDa. It also contain high amount of Methionine, Phenylalanine and Proline which contributed to bitter taste. Mussel hydrolysate produced at pH 7 was the most acceptable and the degree of bitterness was slightly bitter but not exceeded the bitterness of the standard caffeine. These results suggested that green mussel (Perna viridis) hydrolysates have the potential to be applied as a flavoring agent in the food since the bitterness is still in acceptable range.